Awareness and Knowledge of Physical Activity Recommendations in Young Adult Men - Jani P. Vaara; Tommi Vasankari; Harri J. Koski; Heikki Kyröläinen (Frontiers Media S.A., 2019)
Background: There are only a few studies that have assessed awareness and knowledge regarding aerobic type of physical activity (PA) guidelines recommendations, while no previous studies have examined muscular type of activity recommendation guidelines. The aim was to assess knowledge and awareness and study the associations with demographic variables and physical activity and fitness.Methods: Participants were 776 young (age 26 ± 7 years) men. Awareness and knowledge of PA recommendation guidelines were assessed by prompted questionnaires together with demographic variables and physical activity. In addition, physical fitness was measured.Results: Forty percent of the participants reported being aware of the physical activity recommendation. Moreover, 7% correctly identified the recommendations for moderate aerobic physical activity and 25% for muscular type of activity. In addition, 4% correctly identified both aerobic and muscular activity recommendations. Being aware of the PA recommendations was associated with being married or partnered, having higher education level and being more physically active during leisure-time (p < 0.05). Individuals with no awareness of the recommendations had lower results in cardiorespiratory and muscular fitness compared to those being aware (p < 0.05). Being married or partnered was positively associated with the knowledge of the muscular activity recommendations (p < 0.05). Moreover, the individuals with correct knowledge of the PA recommendations had higher levels of muscular fitness (p < 0.05).Conclusion: A low number of individuals are aware or know the physical activity recommendations among young adult men. Therefore, more vigorous attempts to promote physical activity recommendations are needed.